Essential Oils Bioactive Compounds, New Perspectives and Applications - Santana de Oliveira, Mozaniel; Almeida da Costa, Wanessa; Gomes Silva, Sebastião (IntechOpen, 2020)
Essential oils have been used for centuries by communities all over the world in various areas and for various purposes. These include uses in medicine, flavoring, perfumery, cosmetics, insecticides, fungicides, and bactericides, among others. They are natural and biodegradable substances, generally nontoxic or with low toxicity to humans and other animals. Therefore, constant research in these areas represents an alternative for new and more efficient drugs with less side effects as well as obtaining new products and supplies. This book provides a comprehensive overview of the diverse applications of essential oils in a variety of human activities with a focus on the most important evidence-based developments in the various fields of knowledge.